Case Report: Concurrent atrial and ventricular septal defect in a young Sphynx cat - Lee, Jihoon; Oh, Byungkwan; Oh, Sang-Ik; Kim, Bumseok; Park, Hyungjin; Lee, Kichang; Yoon, Hakyoung (Frontiers in Veterinary Science, 2025)
Concurrent atrial septal defect (ASD) and ventricular septal defect (VSD) are rare in cats. A 7-month-old intact female Sphynx cat was presented for evaluation of respiratory distress and exercise intolerance. Thoracic radiographs showed generalized cardiomegaly and pulmonary infiltrates, consistent with cardiogenic pulmonary edema. Transthoracic echocardiography revealed an ostium secundum–type ASD and a perimembranous VSD, with structurally normal atrioventricular valves and annuli. These features supported the diagnosis of concurrent ASD and VSD, rather than an atrioventricular septal defect. Color Doppler echocardiography and agitated saline contrast studies confirmed bidirectional shunting at both defect sites. Additionally, echocardiographic findings were consistent with pulmonary hypertension. As Eisenmenger syndrome was suspected and the owner declined invasive intervention, surgical repair was not performed. Initial treatment with furosemide and supplemental oxygen led to clinical improvement. The owner later discontinued diuretics; however, the cat remained asymptomatic for several months. Cyanosis and erythrocytosis developed approximately 8 months after initial presentation. Follow-up thoracic imaging and Doppler echocardiography demonstrated reduced cardiac silhouette size without recurrent pulmonary edema, right-sided chamber enlargement with right ventricular hypertrophy, and decreased pulmonary-to-systemic flow ratio, consistent with progression of Eisenmenger physiology. Medical management with phlebotomy, sildenafil, clopidogrel, and oxygen supplementation provided temporary stabilization; however, the cat eventually died approximately 1 year after diagnosis, likely due to disease progression and inconsistent therapeutic compliance. Postmortem examination confirmed both septal defects and marked right ventricular hypertrophy, consistent with the ante-mortem imaging findings. Histopathological examination revealed pulmonary vascular remodeling and myocardial fibrosis, indicative of chronic pulmonary hypertension. This report represents the first documented case of concurrent ASD and VSD with Eisenmenger physiology in a cat, with long-term clinical follow-up and postmortem confirmation.